A comprehensive review of ultrasonic patent strategies for mosquito repellence: a landscape analysis - Darren Aviv Dmello; Bharath Raja Guru; Subash Acharya (International Journal of Sustainable Engineering)
Ultrasonic technology provides a safe, eco-friendly, and chemical-free way to keep mosquitoes away, making it a practical option for everyday use in homes and public spaces. Utilising six patent databases (Google Patents, CNIPA, WIPO, EPO, KIPRIS, USPTO) and strict inclusion/exclusion criteria to isolate ultrasonic mosquito repellence patents, over 300 inventions were identified. Patents were evaluated via a qualitative assessment framework rating technical novelty, claimed effectiveness, and sustainability relevance. Devices are classified into wearable, household, entertainment (e.g. Bluetooth speakers, wearable robots), and outdoor categories to enable context-specific design insights. Despite a marked increase in filings since 2003, primarily from China and Korea, this field is built on growing interdisciplinary collaboration needs. Key challenges include wave attenuation, transducer thermal limits, and non-target effects. Eco-friendliness (no chemical emissions, renewable energy integration) and non-invasiveness (minimal contact/disruption) are defined herein. Regulatory oversight varies globally, and standardised safety guidelines are needed. Findings are informative to engineers, public health professionals, and policymakers. Study limitations include reliance on patent claims and language barriers. Nevertheless, the use of ultrasonic technology has the potential to reduce chemical repellent use, lower disease burdens, and improve affordability in low-income regions.